Understanding Monoclonal B Cell Lymphocytosis: An Interplay of Genetic and Microenvironmental Factors - Galigalidou, Chrysi; Zaragoza-Infante, Laura; Iatrou, Anastasia; Chatzidimitriou, Anastasia; Stamatopoulos, Kostas; Agathangelidis, Andreas (Frontiers in Oncology, 2021)
The term monoclonal B-cell lymphocytosis (MBL) describes the presence of a clonal B cell population with a count of less than 5 × 109/L and no symptoms or signs of disease. Based on the B cell count, MBL is further classified into 2 distinct subtypes: ‘low-count’ and ‘high-count’ MBL. High-count MBL shares a series of biological and clinical features with chronic lymphocytic leukemia (CLL), at least of the indolent type, and evolves to CLL requiring treatment at a rate of 1-2% per year, whereas ‘low-count’ MBL seems to be distinct, likely representing an immunological rather than a pre-malignant condition. That notwithstanding, both subtypes of MBL can carry ‘CLL-specific’ genomic aberrations such as cytogenetic abnormalities and gene mutations, yet to a much lesser extent compared to CLL. These findings suggest that such aberrations are mostly relevant for disease progression rather than disease onset, indirectly pointing to microenvironmental drive as a key contributor to the emergence of MBL. Understanding microenvironmental interactions is therefore anticipated to elucidate MBL ontogeny and, most importantly, the relationship between MBL and CLL.